Tax Avoidance During a Pandemic - Pricilia Joice Pesak; Linda Anita Octavia Tanor; Frida Magda Sumual (Journal of International Conference Proceedings (JICP), 2022)
This research empirically want proves that leverage and transfer pricing affect tax avoidance. The phenomenon of tax revenue from the mining sector has been volatile for the past five years so mining companies become the object of research with a research period of 2019 to 2021. This research uses quantitative methods with a causal relationship approach. The sampling technique is purposive sampling by setting several criteria. Based on the established criteria obtained, a sample of 16 companies with the number of data processed was 48 data. The data were analyzed using multiple regression analysis tools with the help of the SPSS 27 application. The results showed that leverage and transfer pricing do not influence tax avoidance. This is due to the research period used by the Covid-19 pandemic which caused restrictions on activities by the government and had an impact on low tax avoidance activities.Keywords: Leverage; Transfer Pricing; Tax Avoidance; Mining Sector; Pandemic.